Children as Social Victims in Charles Dickens’ Oliver Twist and David Copperfield - Rizgar Othman Hamadamin; Shirin Kamal Ahmed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
Charles Dickens (1812-1870) is a remarkable Victorian novelist whose novels are highly admired by critics and still read and academically taught all over the world. Dickens’ novels are considered as literary vehicles by which he managed to criticise both society and government for the suppression, misery, hunger and injustice that were in vague then. His novels give a faithful picture of the Victorian life with all its diversities and complexities. His ideas lead many critics to consider him as a social reformer who called for a radical change in every aspect of people’s life so as to reform society. Dickens’ main concern was children as being an essential part of the society. He focused on the children characters in his novels Oliver Twist and David Copperfield so as to show how childhood was destroyed by the absent justice of both society and government. Dickens himself suffered a lot in his childhood therefore his novels convey true feeling to the extent that his novels are described as being written by a pen made out of his blood.